HOW ARTIFICIAL INTELLIGENCE HELPS PEOPLE IN EVERYDAY LIFE - Xalilova Zarnigor Muhammadjon qizi; Halimjonova Nozanin Abrorjon qizi (TADQIQOTLAR, 2025)
Abstract: In the digital era, cybersecurity has become a fundamental requirement for protecting information, maintaining privacy, and ensuring the functionality of digital systems. As individuals, businesses, and governments increasingly rely on online platforms, cloud services, and connected devices, cyber threats have expanded in both complexity and frequency. These threats include malware attacks, phishing schemes, data breaches, identity theft, and disruptions to critical infrastructure. The consequences of such attacks can be severe, affecting financial stability, national security, social trust, and individual well-being. This paper explores the importance of cybersecurity, examines the most common types of cyber threats, analyzes the societal and economic implications of insecure digital environments, and proposes practical strategies for enhancing digital safety. The study highlights the global need for cybersecurity awareness, stronger regulatory policies, and technological advancements to build a safe and resilient digital future.